2014
DOI: 10.1051/0004-6361/201424379
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum ultraviolet photochemistry of solid acetylene: a multispectral approach

Abstract: Aims. Gas phase acetylene (C 2 H 2 ) and polyynes (H(-C≡C-) m H) are ubiquitous in the interstellar medium. However, astrochemical models systematically underestimate the observed abundances, supporting the idea that enrichment from the solid state takes place. In this laboratory-based study, we investigate the role C 2 H 2 plays in interstellar ice chemistry and we discuss the way its photoproducts may affect gas phase compositions. Methods. C 2 H 2 ice is investigated under vacuum ultraviolet (VUV) irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 67 publications
(90 reference statements)
0
22
0
Order By: Relevance
“…Two prototypical PAHs (pyrene and coronene) were photolyzed using PAH:H 2 O concentrations in the range of 1:30 000 to pure PAH at temperatures between 12 and 125 K. Both the photoproduct composition and the ionization efficiency depends on PAH concentration; the ionization efficiency is 60% in dilute ices, but only 15% in a 1:1000 ice. 150 An increased PAH concentration results in a lower ionization yield due to a combination of an increased recombination rate with increased PAH clustering, and a decreased solvation efficiency of electrons as the OH/e-ratio decreases. OH has a higher electron affinity than H 2 O and the lower PAH-to-H 2 O concentration the higher number of photoproduced electrons will become trapped by OH, increasing the ionization efficiency.…”
Section: Pah Ice Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Two prototypical PAHs (pyrene and coronene) were photolyzed using PAH:H 2 O concentrations in the range of 1:30 000 to pure PAH at temperatures between 12 and 125 K. Both the photoproduct composition and the ionization efficiency depends on PAH concentration; the ionization efficiency is 60% in dilute ices, but only 15% in a 1:1000 ice. 150 An increased PAH concentration results in a lower ionization yield due to a combination of an increased recombination rate with increased PAH clustering, and a decreased solvation efficiency of electrons as the OH/e-ratio decreases. OH has a higher electron affinity than H 2 O and the lower PAH-to-H 2 O concentration the higher number of photoproduced electrons will become trapped by OH, increasing the ionization efficiency.…”
Section: Pah Ice Photochemistrymentioning
confidence: 99%
“…Perhaps by chance, most of them involve simple mixtures of a small hydrocarbon and water, i.e. photolyzed mixtures of CH 4 :H 2 O,137,149 and C 2 H 2 :H 2 O ices 150.…”
mentioning
confidence: 99%
“…It has also been suggested that the formation of benzene can proceed via barrierless radical reaction of ethynyl radical and 1,3-butadiene (30,32). Other studies focused on the formation of benzene and other organic molecules upon irradiation of acetylene ices (22,33). Notwithstanding this progress, the formation of benzene (or its cation) in the ISM is still not fully understood.…”
Section: Significancementioning
confidence: 99%
“…In soot formation, extensive work has been done on the formation of the first aromatic molecule (7). Among the proposed reactions, recombination of propargyl radicals is believed to be an important step that leads (22) to cyclic products such as benzene and C 6 H 5 (23,24). Other important radical reactions include reactions of C 4 H 3 and C 4 H 5 with acetylene (25)(26)(27).…”
mentioning
confidence: 99%
“…Direct solid-state photochemistry of C 2 H 2 required higher energy photons than the 355 nm used in this experiment, as absorption of the acetylene (for the first excited S 0 -S 1 state) starting at wavelength shorter than 237 nm (Couturier-Tamburelli et al, 2015;Malsch et al, 2001). Moreover, the direct acetylene ice photochemistry in the VUV has been experimentally studied, highlighting the formation of longer hydrocarbons molecules, including the formation of polymer (Compagnini et al, 2009;Cuylle et al, 2014). They were not observed in our experiments, excluding direct photochemistry in the acetylene layer, also in agreement with our observation that no significant depletion of C 2 H 2 was detected when pure C 2 H 2 was deposited on a sapphire window.…”
Section: Photochemistry Of Acetylene On Tholinsmentioning
confidence: 98%